The preference of surrogate view among different types of office workers / Tan Hui Ping and Roshida Abdul Majid - Ping, Tan Hui; Abdul Majid, Roshida (Universiti Teknologi MARA, Perak, 2020)
Surrogate view is an element that helps to improve the indoor quality in a windowless office. This study proposed the preference of surrogate view among different types of office workers as an immediate solution in windowless office. Through the survey the most preferred surrogate view among indoor and outdoor workers are the window with sea view 2.95 and 2.86 in the mean. The preferences among worker who spent less than and more than 3 hours are the view to sea which took 2.89 and 2.95 in the mean. The preferences among worker who with and without usage of computer are the view to sea which took 2.96 and 2.88 in the mean.